Using Tritium Isotope in Groundwater to Estimate the Reservoir Capacity at Erbil, Northern Iraq - Mamand, Bruska S.; Mawlood, Dana K. (Iraqi geological journal, 2023)
Tritium is a radioactive isotope of hydrogen in water molecules that can be applied in tracer studies to estimate water residence time. The tritium values of the groundwater in Erbil City and the reservoir's capacity were the main subjects of this investigation. Three sub-basins, including, Kapran (720 km2), Central (1315 km2), and Bashtapa (625 km2) construct Erbil City's groundwater basin. 27 groundwater samples from three sub-basins were taken for oxygen-18, tritium analysis, and measurement of electrical conductivity. Tritium values divided the groundwater reservoirs into three possible groups: pre-bomb groundwaters that have ages older than 70 years due to lower tritium values, contaminated groundwater and mixture of young and old groundwaters. It is adequate to suppose that there were several substantial subsurface retention reservoirs in Dashty-Hawler basin. For instance, if two wells from the Kapan sub-basin were used as a point of reference, well No. 1 in Kalak region would have a tritium value of 1.7 ± 0.72 TU having groundwater that was approximately 16.2 years old. In contrast, the well No. 6 at Grd-Jutyar has a lower tritium value equal to 0.72 ± 0.68 TU indicating a greater residence time of 31.6 years. These two wells have differing reservoir sizes, and well No. 6 has a longer retention basin to store groundwater than well No. 1 According to these findings, younger groundwater and smaller retention basins were indicated by greater tritium levels, whereas older groundwater and larger retention basins were noted by lower tritium levels.